Strategi Guru Pendidikan Agama Islam (PAI) Dalam Meningkatkan Religiusitas Peserta Didik Di SMKN 6 Tangerang - Ika Ika; Rasban Yoyon (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research was motivated by cases that occurred in students who behaved negatively and were lacking in religious matters. PAI teachers are central or central in developing students' religious knowledge and practices. Therefore, PAI teachers are required to implement special strategies to reduce and prevent students from carrying out negative behavior that can harm the school and the community environment. This research uses a qualitative research design. The methods used in this research for data collection techniques are observation, interviews and documentation. The next steps are data reduction, data presentation and verification or drawing conclusions. The results of research on the Teacher Strategy carried out by PAI in Increasing Student Religiosity at SMKN 6 Tangerang are as follows: First, understanding is provided by providing information to students regarding knowledge and the nature of good values from the material presented by educators. This process must be carried out continuously so that students can draw on the messages conveyed by educators. As an example of honesty, cultivation is usually carried out during learning activities by linking material and real life. Second, habituation is a strengthening stage of the previous stage, namely cultivation. The function of habituation is as a bonding tool between students' behavior and themselves, the aim of which is to provide deeper and broader understanding. Third, example is a supporting factor in improving students' religious character. An example will be accepted if it is set by someone close to you. Exemplary really prioritizes aspects of behavior in real action.